Faktor-faktor yang Mempengaruhi Keputusan Menggunakan Jasa Angkutan Bus Pariwisata pada Masa Pandemi - Nur Eva Romadnoni; Hari Rachmadi; Yudi Setiaji (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Factors Affecting The Decision to Use Tourism Bus Transportation Services During Pandemic. The Covid-19 pandemic in early 2020 caused significant losses in various business sectors in Indonesia, particularly in the tourism sector. The factors influencing consumer decisions to use Gege bus transportation services during the Covid-19 pandemic are discussed in this article. During the Covid-19 pandemic, the research population was Gege's transportation tourism service customers, with a total research sample of 30 respondents. Sampling using a random sampling technique without regard for population strata. The variables in this study include price, quality factors, and health protocols, with the consumer's decision to use Gege transportation serving as the determining variable. Multiple linear regression analysis was used to investigate the effect of the variables. These factors have a positive and significant impact on consumer decisions to use services.